Environment-friendly high-performance anhydrous stemming for iron-making blast furnace and preparation method of environment-friendly high-performance anhydrous stemming
By using bauxite, silicon nitride and other aggregates in water-annon gun mud and adding modified coal tar and modified adhesive, the problem of insufficient performance of water-annon gun mud in large and medium-sized blast furnaces is solved, and the effects of high masya value, low linear shrinkage rate and excellent high-temperature flexural strength are achieved, while improving environmental protection performance.
Patent Information
- Application Number
- CN202411392493.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-08
AI Technical Summary
The existing water-announced cannon mud lacks high mastic value, low linear shrinkage and excellent high temperature flexural strength in large and medium-sized blast furnace applications, and traditional binding agents have problems of environmental pollution and health hazards.
Bauxite and silicon nitride are used as aggregates, and silicon nitride micropowder, ferrosilicon nitride micropowder, serpentinite, quartz ceramics, modified coal tar, carbon black, carbon nanotubes and modified adhesives are added. Through the preparation method of modified coal tar and modified adhesive, the adhesion, environmental protection and high temperature resistance of water-annon cannon mud are improved.
It significantly improves the masya value, flexural strength and slag corrosion resistance of waterless cannon mud, reduces the linear shrinkage rate, enhances high-temperature stability and environmental protection performance, and is suitable for high-performance refractory materials in large and medium-sized blast furnaces.
Smart Images

Figure BDA0005072819250000031 
Figure BDA0005072819250000041 
Figure BDA0005072819250000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory materials, and in particular to an environmentally friendly and high-performance anhydrous taphole clay for an iron-making blast furnace and a preparation method thereof. Background Art
[0002] Blast furnace taphole mud is a refractory material used to seal the taphole. It is a key refractory material to ensure the smooth operation of the taphole in front of the furnace. It has the functions of stabilizing the discharge of molten iron and slag formed inside the furnace, extending the depth of the taphole, and protecting the side walls of the furnace. As an amorphous refractory material, blast furnace taphole mud is used in the industry to seal the taphole of the blast furnace, which is an important part to ensure the smooth operation of the blast furnace.
[0003] Cannon clay for blast furnaces is a refractory material used to seal the taphole of blast furnaces during the iron-making process. When in use, it is squeezed into the taphole at a certain pressure using a special equipment for the smelting industry - a mud cannon. Among them, according to the different binders, cannon clay can be divided into water cannon clay and anhydrous cannon clay. The one with organic materials such as tar and resin as binders is called anhydrous cannon clay. Anhydrous cannon clay is mostly used in large and medium-sized blast furnaces with high top pressure and high degree of intensified smelting to meet the needs of blast furnace safety, stable production and high production. As blast furnaces continue to develop towards large-scale, anhydrous cannon clay with excellent comprehensive properties such as high Maxwell value, low linear shrinkage and excellent high-temperature flexural strength has a wider application demand.
[0004] Anhydrous taphole mud is made of high-alumina bauxite clinker, white mud, carbon black, silicon carbide, asphalt, coke powder and other main raw materials, and is compounded with a binder. Traditional anhydrous taphole mud uses tar, anthracene oil and asphalt as binders. The polycyclic aromatic hydrocarbons of these binders evaporate during the heating process to form a pungent sour and spicy smell and yellow smoke, which contains a large amount of carcinogens. Not only is the smoke phenomenon serious, but also in actual use, it causes great harm to the environment and the health of workers. The preparation of a green and environmentally friendly binder with excellent bonding properties is a technical problem that needs to be solved urgently.
[0005] Patent application CN107056260A discloses an environmentally friendly anhydrous taphole mud for plugging the taphole of an iron-making blast furnace and a preparation method thereof, comprising bauxite, recycled silica-molybdenum bricks, coke powder, silica, clay, mica, silicon carbide, ferrosilicon nitride, asphalt, recycled magnesium-carbon bricks, coal tar and resin. The above raw material components are mixed evenly and extruded to obtain a cylindrical product, namely, environmentally friendly anhydrous taphole mud. The resin used is specifically phenolic resin, which improves the high temperature resistance and environmental protection of the binder; however, the phenolic resin has fewer polar groups, which makes the bonding strength between the binder and other materials lower. In addition, how to improve the Maxwell value and linear shrinkage rate of the anhydrous taphole mud is also a technical problem that needs to be solved urgently. Summary of the invention
[0006] The purpose of the present invention is to provide an environmentally friendly and high-performance anhydrous taphole clay for iron-making blast furnaces and a preparation method thereof, so as to solve the technical problems in the prior art that anhydrous taphole clay suitable for large and medium-sized blast furnaces lacks the comprehensive performance of high Maxellen value, low linear shrinkage rate and excellent high-temperature flexural strength, as well as how to improve the adhesion, green environmental protection characteristics and high temperature resistance of the binder used in the anhydrous taphole clay.
[0007] The purpose of the present invention can be achieved by the following technical scheme: an environmentally friendly and high-performance anhydrous taphole mud for an iron-making blast furnace, which comprises, by weight, 30-40 parts of bauxite, 5-10 parts of silicon nitride micropowder, 20-30 parts of silicon nitride, 3-5 parts of ferrosilicon nitride micropowder, 6-10 parts of composite inorganic micropowder, 5-10 parts of modified coal tar, 1-2 parts of carbon black, 3-5 parts of carbon nanotubes and 5-10 parts of modified adhesive.
[0008] The environmentally friendly and high-performance anhydrous taphole mud for iron-making blast furnace prepared by the present invention uses bauxite and silicon nitride as aggregates.
[0009] Furthermore, the preparation method of the modified coal tar comprises the following steps:
[0010] A1, N, N-dimethyl-N-octadecyloxymethylene betaine and hexadecylpropylhydroxysulfobetaine are uniformly mixed in a mass ratio of 1:1 to obtain a composite modifier;
[0011] A2. Coal tar, water and composite modifier are mixed and stirred evenly, and then naturally allowed to stand for 24 hours to obtain modified coal tar.
[0012] Furthermore, in step A2, the usage ratio of coal tar, water and composite modifier is 80g:10-20g:5-10g; the mixing speed is 100-200r / min, and the mixing time is 10-15min.
[0013] Furthermore, the preparation method of the modified adhesive comprises the following steps:
[0014] B1, ethylene glycol, dibutyltin dilaurate, dimethylamide, 2,6-diisocyanate toluene and dimethylglyoxime are uniformly mixed and reacted at 60-70° C. for 1-2 hours to obtain a prepolymer;
[0015] The prepolymer is prepared by reacting dibutyltin dilaurate as a catalyst, dimethylformamide as an organic solvent, dimethylglyoxime, ethylene glycol and 2,6-diisocyanate toluene as monomers.
[0016] Ethylene glycol, 2,6-diisocyanate toluene ester and dimethylglyoxime react to prepare a prepolymer as follows:
[0017]
[0018] B2, mixing lignin and tetrahydrofuran evenly to obtain a lignin solution; filtering the lignin solution with a filter having a pore size of 0.2-0.3 μm to obtain a lignin solution after impurities are removed; injecting the lignin solution after impurities into a dialysis bag, dialyzing it with deionized water for 24 hours, and then freeze-drying it to obtain nano-lignin powder;
[0019] B3. Mix the nanolignin powder and the prepolymer, and continue to react at 60-70°C for 1-2 hours to obtain a modified polyurethane; pour the modified polyurethane into a glass plate, and let it stand at room temperature for 12 hours to obtain a modified adhesive.
[0020] Taking the coniferyl alcohol monomer in the nano-lignin powder as an example, the reaction formula for preparing the modified adhesive by reacting it with the prepolymer is as follows:
[0021]
[0022] Furthermore, in step B1, the amount ratio of ethylene glycol, dibutyltin dilaurate, dimethylamide, 2,6-diisocyanate toluene and dimethylglyoxime is 30g:0.05-0.1g:30-50mL:130-150g:10-20g; in step B2, the amount ratio of lignin and tetrahydrofuran is 5-10g:50mL.
[0023] As another aspect of the present invention, a method for preparing environmentally friendly and high-performance anhydrous taphole mud for an ironmaking blast furnace comprises the following steps:
[0024] S1, silicon nitride is ground to 100-300 mesh to obtain silicon nitride powder; silicon nitride iron is ground to 1-10 μm to obtain silicon nitride iron powder; basic refractory material serpentinite and siliceous refractory material quartz ceramic are mixed in a mass ratio of 1:1 and ground to 200-300 mesh to obtain composite inorganic powder;
[0025] S2, mixing bauxite, silicon nitride powder, silicon nitride, ferrosilicon nitride powder, quartz ceramics, modified coal tar, carbon black, carbon nanotubes and composite inorganic powder to obtain a mixture;
[0026] The bauxite particle size selected in the present invention is 200-300 meshes, wherein the mass percentage of Al2O3 is greater than 80%.
[0027] S3. Add the mixture into a mixer and grind it dry at 55-65°C for 5-10 minutes, then add the modified binder and continue grinding for 20-30 minutes; take samples from the mixer and test the Maxwell value of the samples. When the Maxwell value of the taphole clay is 0.5-1MPa, discharge the material to obtain taphole clay; the taphole clay is extruded through a taphole clay forming machine to obtain environmentally friendly and high-performance anhydrous taphole clay for iron blast furnaces.
[0028] Furthermore, in step S3, the amount of the modified adhesive is 5-10 parts; the box capacity of the cannon mud forming machine is 0.5m 3 , the total power of the motor's spiral blade shaft is 2.5N, and the motor power is 15-20KW.
[0029] The present invention has the following beneficial effects:
[0030] 1. The environmentally friendly and high-performance anhydrous cannon mud for iron-making blast furnaces prepared by the present invention comprises a skeleton, reinforcing additives silicon nitride micropowder and silicon iron nitride micropowder, refractory materials serpentine and quartz ceramics, carbon-based materials and modified adhesives. The environmentally friendly and high-performance anhydrous cannon mud for iron-making blast furnaces prepared by the present invention uses bauxite and silicon nitride as aggregates; bauxite and silicon nitride together constitute the skeleton of the anhydrous cannon mud, prevent the refractory raw materials from over-sintering, and are conducive to drilling. Adding a certain amount of silicon nitride micropowder and silicon iron nitride micropowder as reinforcing additives can significantly improve the compressive strength and flexural strength of the prepared anhydrous cannon mud; silicon nitride in silicon iron nitride is chemically bonded by strong covalent bonds, has high mechanical strength and hardness, and tends to be stable under high temperature environment; the iron in the silicon iron nitride component will form a liquid phase at high temperature, which promotes the sintering of the cannon mud; adding a certain amount of silicon nitride and silicon iron nitride micropowder can improve the cannon mud's resistance to slag iron erosion and slag iron scouring.
[0031] 2. Alkaline refractory materials Serpentinite is mainly composed of serpentine, and the secondary minerals are magnetite, ilmenite, chromite, etc., as well as residual olivine, pyroxene, etc. At 700°C, serpentine dehydrates to form forsterite and amorphous MgSiO3; at 1000°C, amorphous MgSiO3 turns into enstatite; serpentinite, as a calcium-free and rich magnesium oxide source, can improve the desulfurization and alkali removal capacity of slag. Quartz ceramics are made of molten silica, with low linear expansion coefficient and excellent thermal shock resistance. In addition, quartz ceramics can react with CaO, Al2O3, etc. in slag to generate a series of high melting point compounds, which slow down the erosion rate of slag and increase the viscosity of slag, thereby improving the slag resistance of refractory materials.
[0032] 3. Carbon materials include modified coal tar, carbon black and carbon nanotubes. The use of coal tar in anhydrous taphole mud can increase plasticity. During use, coal tar carbonizes at high temperatures to form carbon bonds, which can improve the anhydrous taphole mud's resistance to slag erosion and molten iron scouring. However, coal tar contains a large amount of impurities and polymer compounds, and its carbonization time is slow and not easy to burn. A mixture of two amphoteric surfactants is used as a composite modifier, coal tar and water are mixed, the hydrophilic group acts on the water particles, and the lipophilic group acts on the oil particles, so that the oil-water mixture becomes an emulsion, and modified coal tar is obtained. The water in the modified coal tar will promote the overall combustion performance of the coal tar, thereby improving the combustion characteristics of the anhydrous taphole mud. In addition, coal tar modified by the composite modifier can further improve its own plasticity. After the high-temperature calcination process, the carbon nanotubes will reduce the non-highly graphitized structural substances such as amorphous carbon, and the carbon nanotubes will be further purified; the impurity atoms in the carbon nanotubes will be removed, and thermal compression will occur at the same time, making the crystals in the carbon nanotubes more orderly, which helps to improve the thermal stability and mechanical strength of the carbon nanotubes themselves. In addition, all of the above carbon materials have rich porosity and volume stability. The carbon materials will react complexly with other components of the cannon mud to form carbon bonds, making the overall structure stable.
[0033] 4. In order to bond the above-mentioned skeleton materials, reinforcing aids, alkaline refractory materials and carbon-based materials together, the present invention prepares a high-performance modified adhesive. The modified adhesive prepared by the present invention is specifically a polyurethane material. The polyurethane has high impact resistance and shear strength, and can form a soft-hard transition layer between different substrates to play a role in buffering and shock absorption; different polyurethane molecular chains have isocyanate and carbamate groups. The presence of the above-mentioned strong polar functional groups makes the modified adhesive have high activity and can produce high bonding strength with skeleton materials, reinforcing aids, alkaline refractory materials and carbon-based materials. However, as a binder, polyurethane has the disadvantages of being easily hydrolyzed under high temperature and high humidity conditions and having poor heat resistance. When ethylene glycol is used as a polyol and 2,6-diisocyanate toluene is used as a polyisocyanate-based prepolymer, dimethylglyoxime is introduced for modification. The isocyanate group of 2,6-diisocyanate toluene ester reacts with the oxime group of dimethylglyoxime to obtain a carbamate oxime ester group; the carbamate oxime ester bond is dynamic, and it can reversibly generate an oxime group and an isocyanate group at high temperature; the breaking and reorganization of the dynamic covalent bonds in the polymer chain of the modified adhesive under high temperature environment can induce the dynamic adjustment of the polymer network structure, thereby further improving the bonding performance of the modified adhesive. In addition, the polyurethane prepolymer is modified with nano-lignin. Lignin has high heat resistance, and it has rich benzene ring structures and 3D network structures; lignin is mainly polymerized by monomers through β-aryl ether bonds, CC bonds, etc., and a large number of CC condensation reactions occur between lignin molecules, and it has a large number of benzene ring structures. After heating, lignin with a high benzene ring content can form a carbon network structure through carbonization, so that the obtained cannon mud material has excellent medium-temperature strength and high-temperature strength. DETAILED DESCRIPTION
[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] This embodiment provides a method for preparing modified coal tar for environmentally friendly and high-performance anhydrous taphole mud for ironmaking blast furnaces, comprising the following steps:
[0037] A1, N,N-dimethyl-N-octadecyloxymethylene betaine and hexadecylpropylhydroxysulfobetaine were uniformly mixed in a mass ratio of 1:1 to prepare a composite modifier.
[0038] N, N-dimethyl-N-octadecyloxymethylene betaine and hexadecylpropylhydroxysulfobetaine are uniformly mixed, and a mixture of the two amphoteric surfactants is used as a composite modifier.
[0039] A2. Add 80 g of coal tar and 10 g of water into a 250 mL round-bottom flask, add 5 g of the composite modifier into the round-bottom flask, stir mechanically at 100 r / min for 10 min to mix evenly, and then let it stand naturally for 24 h to obtain modified coal tar.
[0040] Example 2
[0041] This embodiment provides a method for preparing modified coal tar for environmentally friendly and high-performance anhydrous taphole mud for ironmaking blast furnaces, comprising the following steps:
[0042] A1, N,N-dimethyl-N-octadecyloxymethylene betaine and hexadecylpropylhydroxysulfobetaine were uniformly mixed in a mass ratio of 1:1 to prepare a composite modifier.
[0043] A2. Add 80 g of coal tar and 15 g of water into a 250 mL round-bottom flask, add 8 g of the composite modifier into the round-bottom flask, stir mechanically at 150 r / min for 12 min to mix evenly, and then let it stand naturally for 24 h to obtain modified coal tar.
[0044] Example 3
[0045] This embodiment provides a method for preparing modified coal tar for environmentally friendly and high-performance anhydrous taphole mud for ironmaking blast furnaces, comprising the following steps:
[0046] A1, N,N-dimethyl-N-octadecyloxymethylene betaine and hexadecylpropylhydroxysulfobetaine were uniformly mixed in a mass ratio of 1:1 to prepare a composite modifier.
[0047] A2. Add 80 g of coal tar and 20 g of water into a 250 mL round-bottom flask, add 10 g of the composite modifier into the round-bottom flask, stir mechanically at 200 r / min for 15 min to mix evenly, and then let it stand naturally for 24 h to obtain modified coal tar.
[0048] Example 4
[0049] This embodiment provides a method for preparing an environmentally friendly and high-performance modified binder for anhydrous taphole mud for ironmaking blast furnaces, comprising the following steps:
[0050] B1. 30 g of ethylene glycol, 0.05 g of dibutyltin dilaurate, 30 mL of dimethylamide, 130 g of 2,6-toluene diisocyanate and 10 g of dimethylglyoxime were mixed and added into a 250 mL short-necked round-bottom flask. A stirring bar was arranged in the short-necked round-bottom flask. An electric heating jacket was arranged outside the short-necked round-bottom flask. The temperature of the voltage-regulating transformer connected to the electric heating jacket was set to 60° C. The mixture was reacted at 100 r / min for 1 h at this temperature to obtain a prepolymer.
[0051] B2. Evenly mix 5 g of lignin and 50 mL of tetrahydrofuran to obtain a lignin solution; filter the lignin solution with a filter with a pore size of 0.2 μm to obtain a lignin solution after impurities are removed; inject the lignin solution after impurities into a dialysis bag, dialyze it with deionized water for 24 hours, and then freeze-dry it to obtain nano-lignin powder.
[0052] B3. Then, 5 g of the nano-lignin powder was transferred to a short-necked round-bottom flask and the reaction was continued at 60° C. for 1 h to obtain a modified polyurethane; the modified polyurethane was poured into a glass plate and allowed to stand at room temperature for 12 h to obtain a modified adhesive.
[0053] Example 5
[0054] This embodiment provides a method for preparing an environmentally friendly and high-performance modified binder for anhydrous taphole mud for ironmaking blast furnaces, comprising the following steps:
[0055] B1. 30 g of ethylene glycol, 0.08 g of dibutyltin dilaurate, 40 mL of dimethylamide, 140 g of 2,6-toluene diisocyanate and 15 g of dimethylglyoxime were mixed and added into a 250 mL short-necked round-bottom flask. A stirring bar was arranged in the short-necked round-bottom flask. An electric heating jacket was arranged outside the short-necked round-bottom flask. The temperature of the voltage-regulating transformer connected to the electric heating jacket was set to 65° C. The mixture was reacted at 130 r / min for 1.3 h at this temperature to obtain a prepolymer.
[0056] B2. Evenly mix 8 g of lignin and 50 mL of tetrahydrofuran to obtain a lignin solution; filter the lignin solution with a filter with a pore size of 0.2 μm to obtain a lignin solution after impurities are removed; inject the lignin solution after impurities into a dialysis bag, dialyze it with deionized water for 24 hours, and then freeze-dry it to obtain nano-lignin powder.
[0057] B3. Then, 8 g of the nano-lignin powder was transferred to a short-necked round-bottom flask and the reaction was continued at 62° C. for 1.3 h to obtain a modified polyurethane; the modified polyurethane was poured into a glass plate and allowed to stand at room temperature for 12 h to obtain a modified adhesive.
[0058] Example 6
[0059] This embodiment provides a method for preparing an environmentally friendly and high-performance modified binder for anhydrous taphole mud for ironmaking blast furnaces, comprising the following steps:
[0060] B1. 30 g of ethylene glycol, 0.1 g of dibutyltin dilaurate, 50 mL of dimethylamide, 150 g of 2,6-toluene diisocyanate and 20 g of dimethylglyoxime were mixed and added into a 250 mL short-necked round-bottom flask. A stirring bar was arranged in the short-necked round-bottom flask. An electric heating jacket was arranged outside the short-necked round-bottom flask. The temperature of the voltage-regulating transformer connected to the electric heating jacket was set to 70° C. The mixture was reacted at 200 r / min for 2 h at this temperature to obtain a prepolymer.
[0061] B2. Evenly mix 10 g of lignin and 50 mL of tetrahydrofuran to obtain a lignin solution; filter the lignin solution with a filter with a pore size of 0.3 μm to obtain a lignin solution after impurities are removed; inject the lignin solution after impurities into a dialysis bag, dialyze it with deionized water for 24 hours, and then freeze-dry it to obtain nano-lignin powder.
[0062] B3. Then, 10 g of the nano-lignin powder was transferred to a short-necked round-bottom flask and the reaction was continued at 70° C. for 2 h to obtain a modified polyurethane; the modified polyurethane was poured into a glass plate and allowed to stand at room temperature for 12 h to obtain a modified adhesive.
[0063] Example 7
[0064] This embodiment provides a method for preparing environmentally friendly and high-performance anhydrous taphole mud for ironmaking blast furnaces, comprising the following steps:
[0065] S1. Grind silicon nitride to 100 mesh to obtain silicon nitride powder; grind ferrosilicon nitride to 1 μm to obtain ferrosilicon nitride powder. Alkaline refractory material serpentinite and siliceous refractory material quartz ceramic are mixed in a mass ratio of 1:1 and ground to 200 mesh to obtain composite inorganic powder.
[0066] S2. According to weight parts, 30 parts of bauxite, 5 parts of silicon nitride powder, 20 parts of silicon nitride, 3 parts of ferrosilicon nitride powder, 6 parts of composite inorganic powder, 5 parts of modified coal tar prepared in Example 1, 1 part of carbon black and 3 parts of carbon nanotubes are mixed uniformly to obtain a mixture.
[0067] S3. Add the mixture to a mixer and grinder. Set the temperature of the mixer and grind it to 55°C. Dry grind for 5 minutes. Then add 5 parts of the modified adhesive prepared in Example 4 and continue grinding for 20 minutes. Take samples from the mixer and test the Maxwell value of the samples. When the Maxwell value of the cannon mud is 0.5MPa, discharge the material to obtain cannon mud. The cannon mud is transferred to the mud outlet of the YPC-cannon mud forming machine and extruded from the forming tube to obtain a columnar object, which is an environmentally friendly and high-performance anhydrous cannon mud for iron-making blast furnaces. Among them, the box capacity of the cannon mud forming machine is 0.5m3 , the total power of the motor's spiral blade shaft is 2.5N, and the motor power is 15KW.
[0068] Example 8
[0069] This embodiment provides a method for preparing environmentally friendly and high-performance anhydrous taphole mud for ironmaking blast furnaces, comprising the following steps:
[0070] S1. Grind silicon nitride to 200 mesh to obtain silicon nitride powder; grind ferrosilicon nitride to 5 μm to obtain ferrosilicon nitride powder. Alkaline refractory material serpentinite and siliceous refractory material quartz ceramic are mixed in a mass ratio of 1:1 and ground to 300 mesh to obtain composite inorganic powder.
[0071] S2. According to weight parts, 35 parts of bauxite, 6 parts of silicon nitride powder, 25 parts of silicon nitride, 4 parts of ferrosilicon nitride powder, 8 parts of composite inorganic powder, 6 parts of modified coal tar prepared in Example 2, 2 parts of carbon black and 4 parts of carbon nanopowder are mixed uniformly to obtain a mixture.
[0072] S3. Add the mixture to a mixer and grinder. Set the temperature of the mixer and grind it to 60°C. First, dry grind it for 6 minutes. Then, add 6 parts of the modified adhesive prepared in Example 5 and continue grinding for 25 minutes. Take samples from the mixer and test the Maxwell value of the samples. When the Maxwell value of the cannon mud is 0.8MPa, discharge the material to obtain cannon mud. The cannon mud is transferred to the mud mouth of the YPC-cannon mud molding machine and extruded from the molding tube to obtain a columnar object, which is an environmentally friendly and high-performance anhydrous cannon mud for iron-making blast furnaces. Among them, the box capacity of the cannon mud molding machine is 0.5m 3 , the total power of the motor's spiral blade shaft is 2.5N, and the motor power is 16KW.
[0073] Example 9
[0074] This embodiment provides a method for preparing environmentally friendly and high-performance anhydrous taphole mud for ironmaking blast furnaces, comprising the following steps:
[0075] S1. Grind silicon nitride to 300 mesh to obtain silicon nitride powder; grind ferrosilicon nitride to 10 μm to obtain ferrosilicon nitride powder. Alkaline refractory material serpentinite and siliceous refractory material quartz ceramic are mixed in a mass ratio of 1:1 and ground to 300 mesh to obtain composite inorganic powder.
[0076] S2. According to weight parts, 40 parts of bauxite, 10 parts of silicon nitride powder, 30 parts of silicon nitride, 5 parts of ferrosilicon nitride powder, 10 parts of composite inorganic powder, 10 parts of modified coal tar prepared in Example 3, 2 parts of carbon black and 5 parts of carbon nanotubes are mixed uniformly to obtain a mixture.
[0077] S3. Add the mixture to a mixer and grinder. Set the temperature of the mixer and grind it to 65°C. Dry grind for 10 minutes. Then add 10 parts of the modified adhesive prepared in Example 6 and continue grinding for 30 minutes. Take samples from the mixer and test the Maxwell value of the samples. When the Maxwell value of the cannon mud is 1MPa, discharge the material to obtain cannon mud. The cannon mud is transferred to the mud mouth of the YPC-cannon mud forming machine and extruded from the forming tube to obtain a long cylindrical strip, which is an environmentally friendly and high-performance anhydrous cannon mud for iron-making blast furnaces. Among them, the box capacity of the cannon mud forming machine is 0.5m 3 , the total power of the motor's spiral blade shaft is 2.5N, and the motor power is 20KW.
[0078] Comparative Example 1
[0079] The difference between this comparative example and Example 9 is that no carbon nanotubes are added when preparing the mixture.
[0080] Comparative Example 2
[0081] The difference between this comparative example and Example 9 is that when preparing the mixture, the modified coal tar is replaced by coal tar of equal mass.
[0082] Comparative Example 3
[0083] The difference between this comparative example and Example 9 is that no diacetyl oxime was added when preparing the mixture and the prepolymer.
[0084] Comparative Example 4
[0085] The difference between this comparative example and Example 9 is that no composite inorganic micropowder is added when preparing the mixture.
[0086] Performance Test:
[0087] The environmentally friendly and high-performance anhydrous taphole clay for iron-making blast furnaces prepared in Examples 7-9 and Comparative Examples 1-4 was cut to obtain 500 g of cylindrical anhydrous taphole clay as a sample.
[0088] 1. After the anhydrous taphole mud prepared in Examples 7-9 and Comparative Examples 1-4 was placed in an oven at 50°C for 30 minutes, the Maxwell value was tested in a Maxwell value tester.
[0089] 2. According to GB / T5988-2007 "Test method for permanent linear change of refractory materials by heating", the linear shrinkage of the samples after combustion is tested in turn. According to GB / T2997-2015 "Test method for bulk density, apparent porosity and true porosity of close-set refractory products", the apparent porosity of the samples is measured.
[0090] 3. The high temperature flexural strength of the sample was determined according to GB / T3002-2004 “Test method for high temperature flexural strength of refractory materials”. The specific test results are shown in Table 1.
[0091] Table 1-Performance test data of samples
[0092]
[0093] Data Analysis:
[0094] A comparative analysis of the data in Table 1 shows that the environmentally friendly and high-performance anhydrous taphole clay for iron-making blast furnaces prepared in Examples 7-9 of the present invention have strong plasticity, which is manifested by an increase in the Maxwell value, indicating that the modified coal tar can increase the Maxwell value of the taphole clay; however, in Comparative Example 2, the modified coal tar was replaced by coal tar of equal mass, which reduced the plasticity of the coal tar itself, which was manifested by a decrease in the Maxwell value of the prepared anhydrous taphole clay.
[0095] The environmentally friendly and high-performance anhydrous cannon clay for iron-making blast furnaces prepared in Examples 7-9 of the present invention has high shrinkage resistance and strong supporting force, thereby reducing the linear shrinkage rate of the prepared anhydrous cannon clay; however, the linear shrinkage rate of the anhydrous cannon clay prepared in Comparative Example 4 is significantly improved; serpentine and quartz ceramics themselves have low linear expansion coefficients. After removing the composite inorganic micropowder, the linear expansion coefficient of the anhydrous cannon clay prepared in Examples 7-9 is reduced.
[0096] The environmentally friendly and high-performance anhydrous taphole clay for ironmaking blast furnaces prepared in Examples 7-9 of the present invention has a high apparent porosity, which can further improve the apparent porosity. However, in the anhydrous taphole clay prepared in Comparative Example 1, no carbon nanotubes were added; as a carbon-based material, carbon nanotubes have rich porosity and can improve the apparent porosity of the anhydrous taphole clay; therefore, the apparent porosity of the anhydrous taphole clay prepared in Comparative Example 1 is reduced.
[0097] The environmentally friendly and high-performance anhydrous taphole mud for ironmaking blast furnaces prepared in Examples 7-9 of the present invention have excellent mechanical properties, which are manifested as a further increase in the high-temperature flexural strength value. However, in Comparative Example 3, when preparing the modified adhesive, diacetyl oxime was not added, so that the prepared modified adhesive did not have a dynamic reversible bond, which reduced the adhesive performance at high temperature, which was manifested as a decrease in the high-temperature flexural strength value.
[0098] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0099] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0100] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. An environmentally friendly and high-performance anhydrous taphole mud for iron-making blast furnaces, characterized in that: Calculated by weight, it includes 30-40 parts of bauxite, 5-10 parts of silicon nitride powder, 20-30 parts of silicon nitride, 3-5 parts of ferrosilicon nitride powder, 6-10 parts of composite inorganic powder, 5-10 parts of modified coal tar, 1-2 parts of carbon black, 3-5 parts of carbon nanotubes and 5-10 parts of modified adhesive.
2. The environmentally friendly and high-performance anhydrous taphole clay for iron-making blast furnace according to claim 1, characterized in that: The preparation method of the modified coal tar comprises the following steps: A1, N,N-dimethyl-N-octadecyloxymethylene betaine and hexadecyl hydroxypropyl sulfobetaine are uniformly mixed in a mass ratio of 1:1 to obtain a composite modifier; A2. Coal tar, water and composite modifier are mixed and stirred evenly, and then naturally allowed to stand for 24 hours to obtain modified coal tar.
3. The environmentally friendly and high-performance anhydrous taphole clay for iron-making blast furnace according to claim 2, characterized in that: In step A2, the amount ratio of coal tar, water and composite modifier is 80g:10-20g:5-10g; the mixing speed is 100-200r / min, and the mixing time is 10-15min.
4. The environmentally friendly and high-performance anhydrous taphole clay for iron-making blast furnace according to claim 1, characterized in that: The preparation method of the modified adhesive comprises the following steps: B1, ethylene glycol, dibutyltin dilaurate, dimethylamide, 2,6-diisocyanate toluene and dimethylglyoxime are uniformly mixed and reacted at 60-70° C. for 1-2 hours to obtain a prepolymer; B2, mixing lignin and tetrahydrofuran evenly to obtain a lignin solution; filtering the lignin solution with a filter having a pore size of 0.2-0.3 μm to obtain a lignin solution after impurities are removed; injecting the lignin solution after impurities into a dialysis bag, dialyzing it with deionized water for 24 hours, and then freeze-drying it to obtain nano-lignin powder; B3. Mix the nanolignin powder and the prepolymer, and continue to react at 60-70°C for 1-2 hours to obtain a modified polyurethane; pour the modified polyurethane into a glass plate, and let it stand at room temperature for 12 hours to obtain a modified adhesive.
5. The environmentally friendly and high-performance anhydrous taphole clay for iron-making blast furnace according to claim 1, characterized in that: In step B1, the amount ratio of ethylene glycol, dibutyltin dilaurate, dimethylamide, 2,6-diisocyanate toluene and dimethylglyoxime is 30g:0.05-0.1g:30-50mL:130-150g:10-20g; in step B2, the amount ratio of lignin and tetrahydrofuran is 5-10g:50mL.
6. A method for preparing an environmentally friendly and high-performance anhydrous taphole clay for an ironmaking blast furnace as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: S1, silicon nitride is ground to 100-300 mesh to obtain silicon nitride powder; silicon nitride iron is ground to 1-10 μm to obtain silicon nitride iron powder; basic refractory material serpentinite and siliceous refractory material quartz ceramic are mixed in a mass ratio of 1:1 and ground to 200-300 mesh to obtain composite inorganic powder; S2, mixing bauxite, silicon nitride powder, silicon nitride, ferrosilicon nitride powder, composite inorganic powder, carbon black and carbon nanotubes to obtain a mixture; S3. Add the mixture into a mixer and grind it dry at 55-65°C for 5-10 minutes, then add the modified binder and continue grinding for 20-30 minutes; take samples from the mixer and test the Maxwell value of the samples. When the Maxwell value of the taphole clay is 0.5-1MPa, discharge the material to obtain taphole clay; the taphole clay is extruded through a taphole clay forming machine to obtain environmentally friendly and high-performance anhydrous taphole clay for iron blast furnaces.
7. The method for preparing an environmentally friendly and high-performance anhydrous taphole clay for an iron-making blast furnace according to claim 6, characterized in that: In step S3, the amount of modified adhesive is 5-10 parts; the box capacity of the cannon mud forming machine is 0.5m 3 , the total power of the motor's spiral blade shaft is 2.5N, and the motor power is 15-20KW.
Citation Information
Patent Citations
Environment-friendly anhydrous stemming for blocking ironmaking furnace taphole and preparation method thereof
CN107056260A
Environment-friendly anhydrous tamping plug and preparation method thereof
CN103880444A
Binding agent for blast furnace stemming and blast furnace stemming
CN106145966A
Blast furnace iron tapping hole blocking stemming and preparation method thereof
CN108276011A
Novel environment-friendly anhydrous stemming for blast furnace iron notch and preparation method of stemming
CN109776069A